Calcium signals act through histone deacetylase to mediate pronephric kidney morphogenesis. Issue 6 (20th April 2018) - Rothschild, Sarah C.; Lee, Hunter J.; Ingram, Sarah R.; Mohammadi, Daniel K.; Walsh, Gregory S.; Tombes, Robert M.
Abstract : Background: Autosomal dominant polycystic kidney disease is the most common monogenetic kidney disorder and is linked to mutations in PKD1 and PKD2. PKD2, a Ca 2+ ‐conducting TRP channel enriched in ciliated cells and gated by extracellular signals, is necessary to activate the multifunctional Ca 2+/ calmodulin–dependent protein kinase type 2 (CaMK‐II), enabling kidney morphogenesis and cilia stability.Results: In this study, antisense morpholino oligonucleotides and pharmacological compounds were employed to investigate the roles of class II HDAC family members (HDAC 4, 5, and 6) in Zebrafish kidney development. While all three class II HDAC genes were expressed throughout the embryo during early development, HDAC5‐morphant embryos exhibited anterior cysts and destabilized cloacal cilia, similar to PKD2 and CaMK‐II morphants. In contrast, HDAC4‐morphant embryos exhibited elongated cloacal cilia and lacked anterior kidney defects. Suppression of HDAC4 partially reversed the cilia shortening and anterior convolution defects caused by CaMK‐II deficiency, whereas HDAC5 loss exacerbated these defects. EGFP‐HDAC4, but not EGFP‐HDAC5, translocated into the nucleus upon CaMK‐II suppression in pronephric kidney cells.Conclusions: These results support a model by which activated CaMK‐II sequesters HDAC4 in the cytosol to enable primary cilia formation and kidney morphogenesis. Developmental Dynamics 247:807–817, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Hh signal transduction occurs during early SMG development. Loss of SHH activity, via loss of the GLI activator, rather than gain of GLI repressor, is sufficient to cause the SMG aplasia. Loss of cilia on neural crest mesenchyme results in SMG aplasia.